Gastrodiplomacy in Action: The Role of the Indonesian Embassy in Promoting Indonesian Coffee at the Le Printemps du Café Event in Tunis, Tunisia - Glenn Wibisono; Gagih Pradini (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2025)
This research aims to review the role of the Embassy of the Republic of Indonesia in Tunis in promoting Indonesian coffee products at the Le Printemps du Café event held in the Kram Exhibition Centre Tunis, Tunisia. The research method used is a descriptive qualitative approach with data analysis techniques using NVivo. The result using NVivo show that the challenges faced by the Indonesian Embassy in Tunis during their participation in the event included regulatory and policy issues, language barriers, and security concerns at the Indonesian booth. The participation of the Indonesian Embassy in Tunis successfully achieved its goals to promote Indonesian coffee products by adopting the theme “Kopi Indonesia Cita Rasa Surga” and showcasing Indonesian culture through traditional dances. The Indonesian Embassy also established business relationships with coffee industry players and distributors, as evidenced by the visitors' enthusiasm for the showcased Indonesian coffee products. The role of Indonesian embassy in Tunis in promoting Indonesian coffee products at the Le Printemps du Café event includes bridging communication between relevant parties, facilitating, and promoting Indonesia through its coffee products and culture.